1999
DOI: 10.2307/3711937
|View full text |Cite
|
Sign up to set email alerts
|

Secularization in a Context of Advanced Modernity

Abstract: In Europe, the general trend of secula¡ continues, h is attested by the loss of authority of the Catholic church on the societal level and in societal subsystems. This trend is confirmed by the decline of personal religiosity (beliefs, church practice, and moral attitudes). However, the situation is more complex than that: some paradoxes should be stressed. Not infrequently reli~ous authorities ate considerecl to be experts on ethical matters and are requested by civil authorities to ~ve advice; popular religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 4 publications
0
23
0
4
Order By: Relevance
“…The net impact is an increase in the Catholic identity through the recognition of its traditions by its existing adherents. Voye () concludes that there is an increase in invoking Catholicism to affirm the identity of cities, regions, and even the European continent. Consequently, we expect that Catholic CEOs born after 1960 will have a better understanding of the Catholic traditions and teachings.…”
Section: Robustness Testsmentioning
confidence: 99%
“…The net impact is an increase in the Catholic identity through the recognition of its traditions by its existing adherents. Voye () concludes that there is an increase in invoking Catholicism to affirm the identity of cities, regions, and even the European continent. Consequently, we expect that Catholic CEOs born after 1960 will have a better understanding of the Catholic traditions and teachings.…”
Section: Robustness Testsmentioning
confidence: 99%
“…While it is sometimes suggested that some level of secularization in a country is needed in order for there to be respect for human rights (Voye, 1999), this article does not argue that religiosity in and of itself is an inherent obstacle to democracy in general or to human rights more specifically. Religiosity is often translated into political virtue, philanthropy and ethical conduct (Brooks, 2003), and has been found to have a complex effect on support for democracy and tolerance (Ben-Nun Ben-Nun Bloom et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…These results from the empirical literature are consistent with the comparative literature that has linked religious factors to a wide range of conflict types and other political phenomena including legitimacy (Lewy, 1974, 550-551;Johnston and Figa, 1988, 32-34), people's world views (Geertz, 1973;Greely, 1982;Juergensmeyer, 1993), terrorism (Hoffman, 1995, Rapoport, 1984, 1988, genocide (Fein, 1990, 49), ethnic cleansing (Osiander, 2000, 785), conflict management (Appleby, 2000;Gopin, 2000;Abu-Nimer, 2001), identity (Seul, 1999, 558;Voye, 1999), nationalism (Smith, 1999(Smith, , 2000, the formation of the modern Westphalian state system (Philpott, 2000), international diplomacy (Johnston and Sampson, 1994), democracy (Oommen, 1994;and Fox, 1998, 58-59) (Hardacre, 1993), environmentalism (Taylor, 1998), perceptions of the nature of human rights ( Van der Vyver, 1996), public school policy (Wayland, 1997), and economics (Kuran, 1991;Rosser, 1993). Studies based on survey data have also linked religion to political behavior and attitudes.…”
Section: Religion As An Influence On Ethnic Conflictmentioning
confidence: 98%